Integrating Conservative kidney management Options and advance care Planning Education (COPE) into routine CKD care: a protocol for a pilot randomised controlled trial - Scott D Halpern; Michael K Paasche-Orlow; Nwamaka D Eneanya; Taylor L Stallings; Tamar A Klaiman; Margarita Alegria; Ann O’Hare; Nina O’Connor; Laura M Dember (BMJ Open)
Introduction Predialysis education for patients with advanced chronic kidney disease (CKD) typically focuses narrowly on haemodialysis and peritoneal dialysis as future treatment options. However, patients who are older or seriously ill may not want to pursue dialysis and/or may not benefit from this treatment. Conservative kidney management, a reasonable alternative treatment, and advance care planning (ACP) are often left out of patient education and shared decision-making. In this study, we will pilot an educational intervention (Conservative Kidney Management Options and Advance Care Planning Education—COPE) to improve knowledge of conservative kidney management and ACP among patients with advanced CKD who are older and/or have poor functional status.Methods and analysis This is a single-centre pilot randomised controlled trial at an academic centre in Philadelphia, PA. Eligible patients will have: age ≥70 years and/or poor functional status (as defined by Karnofsky Performance Index Score <70), advanced CKD (estimated glomerular filtration rate<20 mL/min/1.73 m2), prefer to speak English during clinical encounters and self-report as black or white race. Enrolled patients will be randomised 1:1, with stratification by race, to receive enhanced usual care or usual care and in-person education about conservative kidney management and ACP (COPE). The primary outcome is change in knowledge of CKM and ACP. We will also explore intervention feasibility and acceptability, change in communication of preferences and differences in the intervention’s effects on knowledge and communication of preferences by race. We will assess outcomes at baseline, immediately post-education and at 2 and 12 weeks.Ethics and dissemination This protocol has been approved by the Institutional Review Board at the University of Pennsylvania. We will obtain written informed consent from all participants. The results from this work will be presented at academic conferences and disseminated through peer-reviewed journals.Trial registration number This trial is registered at ClinicalTrials.gov under NCT03229811.